2014
DOI: 10.1186/s13039-014-0064-9
|View full text |Cite
|
Sign up to set email alerts
|

The first patient with a pure 1p36 microtriplication associated with severe clinical phenotypes

Abstract: BackgroundCopy Number Variants (CNVs) is a new molecular frontier in clinical genetics. CNVs in 1p36 are usually pathogenic and have attracted the attention of cytogeneticists worldwide. None of 1p36 triplication has been reported thus far.ResultsWe present three patients with CNVs in 1p36. Among them one is the first 1p36 tetrasomy due to a pure microtriplication and the other two are 1p36 microdeletion. Traditional chromosome G-banding technique showed a normal karyotype. Single nucleotide polymorphism (SNP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
3
9
0
Order By: Relevance
“…Analysis of PANK4 expression and structure in affected family members may shed light on this issue. PANK4 was found to be expressed in blood (Xu et al., ), and we found that the expression in the blood of our cataract patients was decreased. This result demonstrated that the mutation in the PANK4 gene influences the protein expression.…”
Section: Discussionsupporting
confidence: 57%
“…Analysis of PANK4 expression and structure in affected family members may shed light on this issue. PANK4 was found to be expressed in blood (Xu et al., ), and we found that the expression in the blood of our cataract patients was decreased. This result demonstrated that the mutation in the PANK4 gene influences the protein expression.…”
Section: Discussionsupporting
confidence: 57%
“…A cellular function for HsPANK4 is apparent from two studies that identify congenital disease associated with amplification or reduction of PANK4 expression . In particular, reduced expression due to intronic mutation was causative for congenital cataracts in both humans and mice .…”
Section: Discussionmentioning
confidence: 99%
“…A cellular function for HsPANK4 is apparent from two studies that identify congenital disease associated with amplification or reduction of PANK4 expression. 49,50 In particular, reduced expression due to intronic mutation was causative for congenital cataracts in both humans and mice. 50 HsPANK4 has been reported to directly interact with LDHA, LDHB, HSP90AB1, MYBL2, TUBA1B, NUP133, and GCC1, 51 and these protein-protein interactions are candidates for PANK4 cellular activity.…”
Section: Discussionmentioning
confidence: 99%
“…Giannikou et al 64 reported two individuals with relatively small, de novo, isolated terminal 1p36 duplications (chr1:1–1,565,789 and chr1:1–1,565,607): a 6-month-old male with hypotonia and severe psychomotor delay and a 17-year-old male with growth hormone deficiency, short stature, psychomotor delay, and left ventricular hypertrophy. Subsequently, Xu et al 65 reported an 8-year-old female who carried four copies of approximately 5.28 Mb of the terminal region of 1p36. Her phenotypes included feeding difficulties in infancy, developmental delay, seizures, microcephaly, strabismus, hypertelorism, a low hairline, ear malformations, a broad nasal bridge, wide mouth, thick lips, and prominent incisors.…”
Section: P36 Copy Number Gainsmentioning
confidence: 99%